Improving Knowledge and Skills in Implementing Experimental Methods for Teachers - Melasarianti, Lalita; Pujihastuti, Etin; Derilistiandi, Arfin; Rilastiyobudi, Didik; Widyaningsih, Rindha; Haresyulianti, Uki; Mariasari, Septi; Indahsholikhati, Nur (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
The research results of Melasarianti & Nurhayani (2020) revealed that high school secondary level teachers in the Banyumas Regency area still have low knowledge of experimental research methods. This is proven by the implementation of the 2013 curriculum, teachers are looking for learning innovations to solve problems in teaching and learning activities in the classroom, still using the classroom action research (PTK) method. The low level of teacher knowledge regarding these types of research methods is also experienced by the teachers of SMK N 1 Purwokerto. Evidently, from the results obtained by Melasarianti & Nurhayani (2020) research respondents, as many as 30% came from SMK N 1 Purwokerto, revealing the importance of research methods, especially experimental research, to seek innovation in the learning process. Based on these problems, this activity aims to increase the knowledge and skills of SMK N 1 Purwokerto teachers regarding experimental research methods. The implementation of this activity uses seminar presentation methods, discussions, training and mentoring. Some of the results of this activity are: 1) increasing the knowledge and information of SMK N 1 Purwokerto teachers regarding experimental research methods, 2) increasing the abilities and skills of SMK N1 Purwokerto teachers in compiling titles and formulating problems in experimental research.